Teaching Speaking Report Text through Documentary Video - Moliatul Muslimah; Bustami Usman; Iskandar Abdul Samad (Research in English and Education Journal, 2021)
Speaking is a part of English proficiency that should be mastered by student who learn second language, because the success of mastering second language is measured by the ability of carry out a conversation in form of language. The objective of this research was to prove whether or not the implementation of documentary video can improve the students’ speaking ability. This research was carried out on November 19th up 28th 2019 at SMA Negeri 08 Banda Aceh. This research applied an experimental research design. The research population was eleventh grade students of SMA Negeri 08 Banda Aceh. The sample of this research was selected by using purposive sampling. The instrument of data collection was test which was distributed to the students as pre-test and post-test. The researcher used a statistical analysis to analyze the data. The data were analyzed statistically in order to measure the difference in the achievement of the students in pre-test and post-test. The hypothesis result by using t-test showed that the obtained t-score was higher than t-table (tscore=54.9ttable=1.703), the difference is statistically significant. Therefore, based on the result there is significant improvement before given treatment using documentary video and after treatment. Thus, it can be concluded that documentary video can improve students’ speaking skills and hence Ha is accepted because after  given treatment by documentary video, the students had better achievement in speaking skill.